1993
DOI: 10.1152/ajpheart.1993.264.3.h973
|View full text |Cite
|
Sign up to set email alerts
|

Production of arachidonic acid metabolites in adult rat cardiac myocytes, endothelial cells, and fibroblast-like cells

Abstract: Cells were incubated in the presence of the Ca2+ ionophore A23187 (10 microM) and arachidonic acid (AA, 80 microM). The release of eicosanoids from subcultivated cardiac endothelial and fibroblast-like cells amounted to 23.3 +/- 4.5 and 2.0 +/- 0.4 nmol/mg cellular protein per 30 min, respectively. The release from isolated cardiomyocytes remained below the detection limit of the high-performance liquid chromatography assay (< 0.00015 nmol/assay). When a very sensitive radioimmunoassay was applied, cardiomyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Endothelial cells and fibroblasts exist in close proximity to cardiac myocytes, and the PGs they produce may affect neighboring myocardial cells. Culture medium concentrations of PGF 2␣ from unstimulated primary cultures of three types of adult rat heart cells revealed the following order of production: endothelial cells Ͼ fibroblast-like cells Ͼ myocytes (45). Similar results were reported for neonatal rat fibroblast-like cells and myocytes (46).…”
Section: Discussionsupporting
confidence: 82%
“…Endothelial cells and fibroblasts exist in close proximity to cardiac myocytes, and the PGs they produce may affect neighboring myocardial cells. Culture medium concentrations of PGF 2␣ from unstimulated primary cultures of three types of adult rat heart cells revealed the following order of production: endothelial cells Ͼ fibroblast-like cells Ͼ myocytes (45). Similar results were reported for neonatal rat fibroblast-like cells and myocytes (46).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown increased release of thromboxane A 2 in myocardial ischemia and production of arachidonic metabolites in the ischemic myocardium and in cardiac myocytes under physiological and stimulated conditions. 7,8,10 In addition, Liu et al 11 have recently shown the presence of both COX-1 and COX-2 in the normal and lipopolysaccharide-stimulated rat heart. The latter study supports our findings of induced COX-2 expression in the myocytes and inflammatory cells of patients with heart failure secondary to sepsis.…”
Section: Discussionmentioning
confidence: 97%
“…2 In addition to cytokines, hypoxia, an important feature of ischemic myocardium, induces COX-2 (via NF-B) in cultured endothelial cells independently of other stimuli. 5 Although there have been several studies that demonstrated induction of COX-2 and its association with NF-B activation in various cells, 2,3 and despite the numerous studies describing the production of prostanoids in myocytes, 6,7 whether or not COX-2 is expressed in the human myocardium remains to be elucidated. Interest in COX-2 expression in the failing heart is heightened by the diverse inotropic and morphological effects of prostaglandins on the heart.…”
mentioning
confidence: 99%
“…However, TxA 2 generation has been noted in vascular smooth muscle and endothelial cells of the rat and formation of cys-LTs in endothelium-adherent leukocytes, myocytes, and resident mast cells in the rat heart (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%